Women in Ancient Egypt: determination of legal status and peculiarities of marriage and family relations (Law and Safety, 2023)
The main factors that influenced the formation of the worldview of the ancient Egyptian woman have been investigated. The influence of religion on her understanding of the family, her place and purpose in society has been shown. The main criteria of social differentiation of women have been identified. The primary sources, in particular legal monuments, on the basis of which the legal status of women in Ancient Egypt is shown, have been analysed. The features of marriage and family relations have been characterised. The research is based on the principle of historicism. Historical and comparative as well as historical and genetic methods were used to study the peculiarities of marriage and family relations, normative and comparative and hermeneutical methods were used when working with primary sources. The gender approach has led to a comprehensive study of religious, political, legal norms and social institutions, such as the family, family, culture, and more.Generalisations and conclusions have been made, stating that it was in the religion of Ancient Egypt that the united cults of the divine couple with a son-infant appeared, which became a model for the Egyptians in creating their own family. They were the first among the ancient civilisations to consider the family as the basis of society, which gives us grounds to assert that the family in our modern sense emerged in Ancient Egypt. The social status of women was different. The highest were the ruler’s wives and priestesses, and the lowest were maids and slaves. They had no legal rights and were considered property. However, slaves had the right to personal belongings and to have a family. They faced punishment for ill-treatment. Under certain conditions, slaves could become free and receive the rights of an Egyptian woman. It has been noted that free ancient Egyptian women had almost equal legal rights with men, which distinguishes them from women of other ancient civilisations.It has been emphasized that the study of the status of women and the peculiarities of marriage and family relations in Ancient Egypt allows us to see the historical origins of gender inequality, to understand such basic human values as love, mutual respect, responsibility, tolerance, devotion, etc. which should become the basis for addressing modern gender issues.
Keywords: Ancient Egypt; ancient Egyptian civilisation; woman; religion; priesthood; marriage; family.